TAFSIR AYAT-AYAT QIYAM AL-LAIL: Kajian Komparatif Tafsir Ahkam dan Tafsir Sufi - Ida Ilhafah; Fairuzah (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract Qiyâm al-laîl is considered one of the most important acts of worship and the noblest obedience recommended by Sharia. It contains two inseparable elements: fiqh and Sufistic. Qiyâm al-laîl is prescribed by Sharia as a form of worship while also containing Sufistic elements aimed at getting closer to Allah. This raises the question of how Tafsir Ahkam and Tafsir Sufi interpret the verses related to qiyâm al-laîl? This article aims to examine qiyâm al-laîl from the perspectives of Sufi Ulama and Ahkam Ulama and compare the two. The study employs qualitative library research using descriptive-analytical methods to explore the data obtained. The results of the study indicate that qiyâm al-laîl involves enlivening the night with primary practices such as tahajjud prayers, witr, reading the Qur'an, dhikr, and contemplation with a sense of solemnity, tawadhu', thuma'ninah, and others. Secondly, it is understood by Ahkam Ulama that qiyâm al-laîl is a command from Allah to the Prophet and his ummah, in addition to obligatory worship. Thirdly, Sufi Ulama interpret the verses of qiyâm al-laîl and conclude that becoming accustomed to waking up at night to pray to Allah is one of the exercises that revitalizes the heart, brings peace of mind, and brings one closer to God. The grand conclusion is that the interpretations of the two Ulama with different backgrounds have a complementary relationship. Both refer to clear sources, but their different scientific backgrounds lead to differing interpretations still within Islam's realm. Keywords: Qiyâm al-Laîl, Tafsir Ahkam, and Tafsir Sufi